Регулювання конкурентоспроможності вищої освіти України в контексті сучасних тенденцій, зокрема соціального партнерства - Трохимець, О. І.; Ткачук, О. В.; Trokhymets, O.; Tkachuk, O. (My University, 2018)
В статті висвітлено роль процесу регулювання у сфері вищої освіти з урахуванням соціального партнерства, яке виступає одним з типів взаємодії освітніх установ з усіма суб'єктами ринку праці, що направлені на максимальне узгодження та реалізації інтересів всіх учасників даного процесу. Визначено принципи тристороннього співробітництва – державно-приватного партнерства з вищими закладами освіти. Окреслено три основні моделі партнерства між державою, бізнес-середовищем та вищими закладами освіти. The article highlights the role of the regulatory process in the field of higher education, taking into account social partnership, which serves as one of the types of interaction between educational institutions and all actors of the labor market, aimed at maximizing the harmonization and realization of the interests of all participants in this process. The principles of trilateral cooperation – public-private partnership with higher education institutions are determined. Three main models of partnership between the state, the business environment and higher education institutions are outlined.
Regulation of the competitiveness of higher education of Ukraine in the context of the current tendencies, considering social partnership
Keywords: вища освіта; державне регулювання; соціальне партнерство; бізнес-середовище; освітнє середовище; бізнес-інкубатор; higher education; social partnership; educational environment; business incubator; state regulation; business environment